Open Source Software Superstream Series Python-Tips and Tricks, Machine Learning, and What's New in 3.9 and Beyond - Hightower, Kelsey; Indrasiri, Kasun; Das, Kushal; Morehouse-Vacaral, Emily; Salgado, Pablo (O'Reilly Media, Inc., 2021)
Python is the most popular language for data science and machine and deep learning, and it's become a favorite among web developers due to its versatility, vast library ecosystem, and high-performance applications. Python's many new features will ensure it remains the language of choice for these robust communities, even as we approach its 30-year anniversary. Join members of the Python community as they share expert perspectives on topics ranging from machine learning to microservices. Discover how to implement Python's newest features to optimize performance and take your Python code to the next level. About the OSCON Superstream Series: Each day in the four-part OSCON Superstream Series covers a different programming language and its ecosystem, with unique sessions including keynotes from language luminaries, debates on controversial topics, and hands-on coding talks. And they're packed with insights from innovators and the latest tools and technologies to help you stay ahead of it all. What you'll learn-and how you can apply it Explore Python's newest features Understand how Python can be applied in machine learning Learn how to use gRPC with polyglot technologies including Python Implement Python's newest features to optimize performance This Superstream is for you because ... You're a Python developer looking to improve your skills and awareness of new practices and technologies. You're a developer in another programming language and are curious about how Python can improve the performance of your applications. You're an experienced developer who wants to learn new tools and techniques from expert programmers and software developers. Prerequisites:, /p> Come with your questions Have a pen and paper handy to capture notes, insights, and inspiration.